2012
DOI: 10.5194/gmd-5-313-2012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parallel computational uncertainty on simulations of the Coupled General Climate Model

Abstract: Abstract. This paper investigates the impact of the parallel computational uncertainty due to the round-off error on climate simulations using the Community Climate System Model Version 3 (CCSM3). A series of sensitivity experiments have been conducted and the analyses are focused on the Global and Nino3.4 average sea surface temperatures (SST). For the monthly time series, it is shown that the amplitude of the deviation induced by the parallel computational uncertainty is the same order as that of the climate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Song et al, 2012) and can be problematic: Fig. 21 shows results from two "identical" integrations applying the default (but rather aggressive) Intel fp-model compiler option.…”
Section: Computational Uncertaintymentioning
confidence: 99%
“…Song et al, 2012) and can be problematic: Fig. 21 shows results from two "identical" integrations applying the default (but rather aggressive) Intel fp-model compiler option.…”
Section: Computational Uncertaintymentioning
confidence: 99%
“…FGOALS-g2 is a fully coupled CSM consisting of the atmosphere model the Grid-point Atmospheric Model of IAP LASG version 2 (GAMIL2) (Li et al, 2013b), ocean model LASG/IAP Climate System Ocean Model Version 2 (LI-COM2) (Liu et al, 2004), land surface model Community Land Model Version 3 (CLM3) (Oleson et al, 2004), and an improved version (Wang et al, 2009;Liu, 2010) of the sea ice model Los Alamos Sea Ice Model version 4 (CICE4) (http://oceans11.lanl.gov/trac/CICE). It participated in the Coupled Model Intercomparison Project Phase 5 (CMIP5) and is widely used for scientific research.…”
Section: Models and Simulationsmentioning
confidence: 99%
“…The first challenge concerns reproducibility of simulation results. Due to the chaotic nature of the climate system, more and more studies have shown that trivial round-off errors can trigger significant changes in simulation results of Earth system modeling (Hong et al, 2013;Liu et al, 2015b;Song et al, 2012). Due to the differences of performance optimization schemes among different compiling setups, a change of compiling setups potentially introduces round-off errors.…”
Section: Introductionmentioning
confidence: 99%
“…The first challenge is that new heavy burdens would be introduced to scientists. As bitwise results are determined by the whole simulation setting (including the model code, input data, parameter setting, computing environment, etc., Ford et al, 2012) and are very sensitive to round-off errors resulting from the computing environment 10 (Monniaux, 2008;Song et al, 2012;Hong et al, 2013), it requires original scientists to preserve the whole simulation setting and fellow scientists to recreate almost exactly the same simulation setting during a reproduction.…”
Section: Introductionmentioning
confidence: 99%